Binomial Transform of the Generalized Third Order Pell Sequence - Soykan, Yüksel (Communications in Mathematics and Applications, 2021)
In this paper, we define the binomial transform of the generalized third order Pell sequence and as special cases, the binomial transform of the third order Pell, third Order Pell-Lucas and modified third order Pell sequences will be introduced. We investigate their properties in details.
Keywords: Binomial transform; Third order Pell sequence; Third order Pell numbers; Third order Pell-Lucas sequence; Third order Pell-Lucas numbers